Microwave-Assisted Synthesis of Layered Double Hydroxides and Their Nanocomposites - Ow Wee, Shing Tat (1999)
A senes of hydrotalcite (HT) compounds of the type {Mg1_.rAl,(OH)2}[CO3]1.x12 mH2O had been synthesised using conventional co-precipitation method with Rd15 = Mg/ Al=1 to 10 m order to establish the relationship between composition and the basic properties it was found that pure HT compounds were obtained in the range of Rd15 =2 to 4. The materials were also synthesised by microwave-assisted method using a home cooking microwave oven at various ageing tunes, from 0 5 to 10.0 minutes.The discharged ratio of Rd15 = 3, 4, and 6 were chosen in this study. The resulting synthetic materials afford well-crystallised hydrotalcite even at a very short microwave exposure tune of about 60 minutes as compared With the conventional method that took about 18hrs. However, the conventional method gave good crystallimty. On the other hand, the microwave-assisted method gave better pore size distribution as compared to the conventional method. Better crystallImty was observed as the exposure time mcreased for all Rd15 Structural charactensations were done by powder X-ray diffraction (PXRD). The gram sizes and crystal stram of the materials using PXRD were calculated. Modification of hydrotalcite had also been done by replacing its among With anthraqumone-2,6-disulfanate ions (AQ26), which were present in the mterlayer of brucitelike ([Mg1-,AI.,(OH)2]") and [Zn1-.,Alx(OH)2]")...